2017
DOI: 10.1155/2017/9162095
|View full text |Cite
|
Sign up to set email alerts
|

Public Medical Preparedness at the “Swiss Wrestling and Alpine Games 2013”: Descriptive Analysis of 1,533 Patients Treated at the Largest 3-Day Sporting Event in Switzerland

Abstract: Introduction. Medical preparedness at mass gatherings is challenging, as little is known about the optimal planning. Most studies and case reports are based on mass casualty incidents, so the results cannot be extrapolated to mass gatherings. Aim of this study was to evaluate the preclinical medical structure and the frequency of specific injuries and medical emergencies during the event. Methods. Retrospective analysis of a prospectively collected database. Three on-site medical assistance points were set up,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Many studies included values such as the number of injuries, deaths, and hospitalizations; however, many studies were also found that did not provide these values. 34,60,[71][72][73] In a study conducting a retrospective analysis of patient admissions over seven years, the number of attendees attending each year was provided, but the total number of attendees was not given. Moreover, PPR and TTHR values were provided on average, but they were not detailed for each specific year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies included values such as the number of injuries, deaths, and hospitalizations; however, many studies were also found that did not provide these values. 34,60,[71][72][73] In a study conducting a retrospective analysis of patient admissions over seven years, the number of attendees attending each year was provided, but the total number of attendees was not given. Moreover, PPR and TTHR values were provided on average, but they were not detailed for each specific year.…”
Section: Discussionmentioning
confidence: 99%
“…7,20 The MUR is calculated by dividing the number of individuals seeking medical care by the total attendance for that event and is typically reported as a rate in patients per 10,000 (PPTT). 34,53,60 The PPR also is referred to as the MUR, but PPR may be limited in some studies to presentations to medical services and exclude first aid and other prehospital care presentations. 68 Therefore, it can be said that MUR encompasses the total patient presentations, including all presentations delivered by first aid providers and professional health care workers.…”
Section: Rate Of Using Start-finish Medical Post (Usfmp)-start-finishmentioning
confidence: 99%
“…Only two studies reported on whether drugs and alcohol were precipitating factors in ambulance transfers. 15,22 From the alpine games, drug and alcohol intoxication contributed to over three percent of all ambulance transfers to hospital. 22 Intoxication was not a cause for ambulance transfers from a horse racing event, however, it did contribute to 25% of transfers from a rugby game.…”
Section: A Prehospital Perspectivementioning
confidence: 99%
“…15,22 From the alpine games, drug and alcohol intoxication contributed to over three percent of all ambulance transfers to hospital. 22 Intoxication was not a cause for ambulance transfers from a horse racing event, however, it did contribute to 25% of transfers from a rugby game. 15 Records An ED Perspective Two of the included papers described the impact of sporting MGEs from an ED perspective (Table 4 25,26 ).…”
Section: A Prehospital Perspectivementioning
confidence: 99%
“…Maurer's formula has been used to define the quality and number of resources to be deployed at the time of event [22]. These conceptual models are based on the idea that MG health can be understood as an interrelationship between three domains: (1) the biomedical, (2) the environmental, and (3) the psychosocial.…”
Section: Introductionmentioning
confidence: 99%